Potency of Turmeric Extract (Curcuma domestica Val.) with Virgin Coconut Oil (VCO) Against Incision Wound Healing - Atifah, Yusni; Kurnia, Aifa (Biology, Medicine, & Natural Product Chemistry, 2024)
Wounds are damage or loss of body tissues that occur due to a factor that interferes with the body's protective system. One example of an open wound is an incision where there is a linear tear in the skin and underlying tissue. One natural ingredient that has potential as an alternative treatment for cut wounds is turmeric and VCO. The part of turmeric contains curcumin to accelerate wound healing and VCO contains lauric acid which functions as an antibacterial.  The purpose of this study was to determine the effect of the combination of turmeric extract (Curcuma domestica Val.) with Virgin Coconut Oil (VCO) on the percentage and healing time of incision wounds in male mice (Mus musculus L.). This research is an experimental study. The research was conducted from October to December 2023 at the Animal House and Research Laboratory of the Department of Biology, Faculty of Mathematics and Natural Sciences, Padang State University. The design used is a Complete Randomized Design (RAL) with 5 (five) treatments and 5 (five) repeats. The data obtained were analyzed using the ANOVA (Analysis of Variance) test using the SPSS 22 application. The results showed that the combination of turmeric extract (Curcuma domestica Val.) with Virgin Coconut Oil (VCO) affected the percentage and time of incision wound closure in male mice (Mus musculus L.). The best combination of turmeric extract with VCO is a ratio of 2:1.